Analisis Komparatif Kinerja Keuangan Sebelum Dan Sesudah Akuisisi (Studi Kasus: PT Sumber Alfaria Trijaya Tbk Periode 2017-2018 Dan 2020-2021) - Rini Oktaviani Putri; Puan Maharanti; Ratih Kusumastuti (Universitas 45 Surabaya, 2023)
Acquisition is a type of company development strategy employed by corporations. The financial success of the company is impacted by acquisitions. An organization can determine the outcomes of its operational actions by its financial performance, which is represented by numerical figures. Financial ratios can be used to confirm financial performance. In this study, financial performance for the years 2017–2018 and 2020–2021 is measured and contrasted before and after PT Sumber Alfaria Trijaya Tbk was acquired. Descriptive and comparative methods, as well as quantitative methodology, are used in this kind of research. Secondary data is derived from the financial accounts (annual report). The current ratio and the return on investment before and after the acquisition differed significantly, according to the analysis's findings. As a ratio of debt to total assets and sales before and after the transaction, there has been no discernible change.